1995
DOI: 10.1073/pnas.92.5.1465
|View full text |Cite
|
Sign up to set email alerts
|

A mutation in the epidermal growth factor receptor in waved-2 mice has a profound effect on receptor biochemistry that results in impaired lactation.

Abstract: The mutant mouse waved-2 (wa-2) is strikingly similar to transforming growth factor a-deficient mice generated by gene targeting in embryonic stem cells. We confirm that wa-2 is a point mutation (T --G resulting in a valine --glycine substitution at residue 743) in the gene encoding the epidermal growth factor (EGF) receptor. wa-2 fibroblastic cells lack high-affinity binding sites for EGF, and the rate of internalization of EGF is retarded. Although the tyrosine kinase activity of wa-2 EGF receptors is signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
126
1

Year Published

1996
1996
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(138 citation statements)
references
References 30 publications
9
126
1
Order By: Relevance
“…For example, the mammary-specific knockout of ErbB4 resulted in a profound defect in functional differentiation of mammary epithelium (Long et al, 2003). Moreover, the waved-2 mice, which harbor an impaired EGFR allele, also have lactational defects (Fowler et al, 1995). Taken together with our observations, these data suggest that ErbB4 homodimers or heterodimers consisting of EGFR or ErbB3 but not ErbB2 are important EGFR family receptor combinations for functional differentiation and lactation.…”
supporting
confidence: 70%
See 1 more Smart Citation
“…For example, the mammary-specific knockout of ErbB4 resulted in a profound defect in functional differentiation of mammary epithelium (Long et al, 2003). Moreover, the waved-2 mice, which harbor an impaired EGFR allele, also have lactational defects (Fowler et al, 1995). Taken together with our observations, these data suggest that ErbB4 homodimers or heterodimers consisting of EGFR or ErbB3 but not ErbB2 are important EGFR family receptor combinations for functional differentiation and lactation.…”
supporting
confidence: 70%
“…For example, waved-2 mice carrying a kinase impaired EGFR allele exhibit comparable ductal defects (Fowler et al, 1995). However in contrast to cell autonomous requirement for ErbB2 function, transplantation of EGFR null tissues has revealed that EGFR functions primarily in the stroma during the phase of ductal outgrowth (Sebastian et al, 1998).…”
mentioning
confidence: 99%
“…There are a number of observations that favour the correlation between EGFR affinity and biological effect (Defize et al, 1989;Bellot et al, 1990). Others have found a similar correlation between the affinity state of the EGFR and proliferative effect after growth factor administration (Fowler et al, 1995). It has been shown that a T → G point mutation in the EGFR at residue 743 results in the wa-2 phenotype (Luetteke et al, 1994;Fowler et al, 1995), which is characterized by loss of high-affinity EGFRs and a requirement for a 20-fold higher concentration of EGF to achieve the same effect on DNA replication as seen with the cells bearing wild-type EGFRs (Fowler et al, 1995).…”
Section: Discussionmentioning
confidence: 97%
“…Notably, in vivo analyses revealed that mammary development was impaired in waved-2 mice that harbored a mutant (kinase-deficient) EGFR on all cells [21,22] and similarly impaired in transgenic mice that expressed a dominant-negative EGFR on their mammary epithelial cells alone [23], suggesting that epithelial EGFR played a key role. However, EGFR is also abundant within the mammary stroma [24,25].…”
Section: Stromal Egfr Is Required For Mammary Developmentmentioning
confidence: 99%